Ambient air pollution exposure and risk of migraine: Synergistic effect with high temperature. (December 2018) - Lee, Hyewon; Myung, Woojae; Cheong, Hae-Kwan; Yi, Seung-Muk; Hong, Yun-Chul; Cho, Sung-Il; Kim, Ho
Abstract: Background: Migraine is a chronic and agonizing neurological disorder prevalent worldwide. Although its pathogenesis remains unclear, limited evidence exists on the role of air pollution. Objective: We aimed to assess the association of short-term air pollution exposure with migraine in conjunction with the synergistic effect of temperature. Methods: We identified 18, 921 patients who visited emergency departments (EDs) for migraine as a primary disease in Seoul from the national emergency database between 2008 and 2014. We conducted a time-stratified, case-crossover analysis to compare levels of particles <2.5 μm (PM2.5 ), particles <10 μm (PM10 ), nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ), ozone (O3 ), and carbon monoxide (CO) on ED visit days and those on the control days matched to day of the week, month, and year. We evaluated the synergistic effects of air pollution and temperature using an interaction term. Results: Higher air pollution levels were significantly associated with risk of migraine over various lag structures. In the best fitting lags, the odds ratio (OR) associated with an interquartile range increase of PM2.5, PM10, NO2, O3, and CO was 1.031 (95% CI: 1.010–1.053), 1.032 (95% CI: 1.007–1.057), 1.053 (95% CI: 1.022–1.085), 1.034 (95% CI: 1.001–1.067), and 1.029 (95% CI: 1.005–1.053), respectively. The SO2 effect was positive but not significant (OR 1.019 [95% CI: 0.991–1.047]). The PM effect was significantly stronger on high-temperature days (above the 75th percentile) than on low-temperature days (PM2.5, high: OR 1.068, low: OR 1.021, P interact  = 0.03; PM10, high: OR 1.066, low: OR 1.014, P interact  = 0.02). Conclusion: Our study provides new evidence that air pollution exposure may trigger migraine especially on high-temperature days, and this finding may contribute in establishing preventive measures against migraine. Highlights: We assessed a short-term association between ambient air pollution and migraine. We examined a synergistic effect of air pollution and temperature on migraine. PM2.5, PM10, NO2, O3, and CO significantly increased the risk of migraine. The PM2.5 and PM10 effects were significantly stronger on high-temperature days.